(untitled) (Research, Society and Development, 2021)
Halitosis is a condition with a multifactorial etiology, popularly known as an unpleasant smell that is exhaled through the oral and nasal cavity. The objective of this work is to evaluate the level of knowledge of undergraduates and graduate students about the definition of halitosis, treatment and diagnosis of the different types that exist. The methodology used consists of a cross-sectional study through an online questionnaire, where data are extracted that make it possible to identify whether students have adequate knowledge about the diagnosis, causes and possible treatments for halitosis. A literature review was carried out for theoretical knowledge and preparation of the electronic questionnaire. After analyzing the data, it was observed that 74% of the participants were female. Among the results found, it is possible to highlight: 74% considered halitosis a disease, 65% claim to know how to diagnose halitosis. Regarding the causes of halitosis: 60% answered that it is oral origin, 41% physiological, 51% pathological and systemic, 43% checked all the options, and 51% answered it had multifactorial causes. About the best forms of treatment: 79% considered the option of oral hygiene and the use of dental floss, and avoiding foods such as onions and garlic, 57% think there are devices for diagnosing halitosis, and 86% assume that saliva compromises bad breath. It can be said that halitosis is a condition that affects thousands of people worldwide, and although many dentistry students believe they know about the subject, through research, a lack of scientific knowledge on the subject was verified, requiring new actions to improve the information.